(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In the digital age, social networks have become an integral part of our lives. They offer us a platform to connect with friends, family, and even strangers from around the world. However, with their increasing popularity, an alarming issue has emerged – addiction to social networks. This article aims to shed light on the addictive nature of social networks, its impact on individuals, and strategies to manage this modern-day challenge.